Analysis of the Effectiveness of Road Equipment to Support Rider Safety in Educational Areas (Case Study: Jl. Prof. Moh Yamin) - Syah, Angga David Maolana; Adha, Ahmad Syarif Shaiha; Wijayanti, Fausta Patricia; Hidayat, Dwi Wahyu (Portal: Jurnal Teknik Sipil, 2025)
The Education Zone is an area with a very high intensity of activity for both drivers and pedestrians, especially among students, hence it requires adequate road facilities to enhance the safety of road users. This study aims to analyze the effectiveness of road facilities found in the Education Zone such as traffic signs, road markings, warning lights, bus stops, and speed control devices on Jl. Prof. Moh. Yamin. The methods used include field observations and analysis of driver compliance with the available road facilities. The results of this study show that the existing road facilities, such as traffic signs and road markings, are less effective in improving safety for drivers and road users.. In addition, the level of compliance among drivers regarding road equipment is very minimal, especially during peak hours. This study recommends improvements and additions to the road equipment according to the needs of the Educational Area to minimize accidents and enhance safety for drivers and road users. This research is expected to serve as a reference for designing a safe traffic movement system in the Educational Area.